Treatment of Bilateral Venous Thrombosis in a Patient with Aplasia of the Inferior Vena Cava - Khrebtiy, Yaroslav V.; Tsyhalko, Denys V.; Melnychuk, Mykola O. (Ukrainian Journal of Cardiovascular Surgery, 2022)
The aim. In the treatment of venous thromboembolism, a special place is occupied by patients with congenital anomalies of the development of the inferior vena cava (IVC). To date, only single cases of treatment of this pathology have been described in the literature. Studying the experience of treating patients with congenital anomalies of the IVC will allow to improve the results of treatment of this category of patients. Materials and methods. Patient B., a 36-year-old man, applied to the vascular surgery clinic of the Vinnytsia Regional Pyrohov Clinical Hospital in July 2010 with complaints of pain, swelling, cyanosis of both lower extremities, which bothered the patient for about 10 days. The patient had no history of venous insufficiency of both lower extremities. An objective examination revealed cyanosis and swelling of both lower extremities. A duplex scan of both lower extremities revealed hyperechoic iliofemoral thrombosis of both lower extremities. Aplasia of the IVC was diagnosed. The common iliac veins on both sides formed a collateral that flowed into the left renal vein. The infrarenal segment of the inferior vena cava was absent. Thrombosis spread from tibial to popliteal, femoral, iliac veins with venous collateral thrombosis up to the level of the left renal vein. The patient received enoxaparin at a dose of 1 mg per kg of body weight twice a day for 7 days with subsequent transition to warfarin under the control of international normalized ratio. Warfarin was prescribed from a starting dose of 5 mg with subsequent control of international normalized ratio in the range of 2.0-3.0. Venotonic and anti-inflammatory drugs were also prescribed. In combination with drug therapy, class 2 elastic compression stockings were recommended. After the treatment, the patient’s condition improved, swelling and cyanosis of both lower extremities regressed. Repeated duplex scanning at the discharge of the patient from the hospital after 7 days showed signs of initial recanalization of the affected venous segments and no progression of thrombosis. Conclusions. Thus, this clinical case showed that the use of anticoagulant therapy allows to obtain satisfactory results in the treatment of patients with congenital anomalies of the development of IVC, to avoid the development of pulmonary embolism and other life-threatening conditions. At the same time, such patients need regular follow-up examinations in order to adjust the treatment and prevent the development of IVC syndrome.